Implementation of consumer behavior process: a study on Melaka International Trade Center (MITC) / Mohd Khairul Amri Zakaria - Zakaria, Mohd Khairul Amri (Faculty of Business and Management, 2010)
The issue for this report is to knowing the level of customer loyalty in the services made by Melaka International Trade Center (MITC). Since the MITC performance is depends on the sales of renting the place, it is necessary to keep the customer to make their frequent purchase on MITC. This report will analyze and identify what can be done to create customer loyalty. The purpose for making this study is to determine what action should be taken by the members of marketing department in Melaka International Trade Center (MITC) in order to better strategize their marketing strategy. In addition, this study also will help to gain a better knowledge and understanding on consumer decision process. The consumer decision process will help the marketers to know the step and actions taken by customer in order for them to make a purchase decision. In order to complete this study, several method on research methodology were taken to finalize and make conclusion on the findings of the result. The research methodology consists on data collection method, data presentation and work schedule were deeply discussed on the latter chapter. As for this study, it will be expected that the customer loyalty could be derive on customers of Melaka International Trade Center (MITC) based on the consumer decision behavior analysis. The study will compare the current marketing strategy being implied by marketing staff of MITC based on consumer decision behavior with the actual technique suggested by scholars. Besides that, the result of this study will prove that there are flaws on strategy implied by marketers of Melaka International Trade Center.